2010
DOI: 10.1002/etc.364
|View full text |Cite
|
Sign up to set email alerts
|

Response of white sucker (Catostomus commersoni) to pulp and paper mill effluent in the Androscoggin River, Maine, USA

Abstract: Adverse effects of pulp and paper mill effluent on fish populations have been well documented in many countries over the last two decades. Some of the initial studies were at mills with conventional chlorine bleaching and no secondary effluent treatment. Following installation of secondary treatment, changes in bleaching technology to elemental chlorine-free bleaching, and other process changes, adverse effects on fish were reduced or eliminated at some mills. Because no two mills are exactly alike, it is diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…While improvements have been observed after temporary closures (Bowron et al 2009) and maintenance shutdowns (Munkittrick et al 1992) at some mills, they are not always clearly demonstrated. Similarly, contrasting patterns have also been observed after treatment and process upgrades (Servos et al 1997; Janz et al 2001; Mower et al 2011), including persistence of some signals in fish captured at MAT‐EXP in earlier studies (Munkittrick et al 1998; Arciszewski et al 2015). Our data are no exception.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…While improvements have been observed after temporary closures (Bowron et al 2009) and maintenance shutdowns (Munkittrick et al 1992) at some mills, they are not always clearly demonstrated. Similarly, contrasting patterns have also been observed after treatment and process upgrades (Servos et al 1997; Janz et al 2001; Mower et al 2011), including persistence of some signals in fish captured at MAT‐EXP in earlier studies (Munkittrick et al 1998; Arciszewski et al 2015). Our data are no exception.…”
Section: Discussionmentioning
confidence: 93%
“…Studies of recovery have been done at multiple pulp mills but historically examined process changes, treatment upgrades, and temporary closures. Studies after process changes and treatment upgrades have indicated re-occupation by species (Cross and Ellis 1981), whereas others have shown reduced indications of exposure (Bowron et al 2009;Mower et al 2011). However, elimination of impacts is not always observed during these interventions (Munkttrick et al 1992;Munkittrick et al 1997;Bowron et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In studies at other mills, improved reproductive performance was generally associated with reduced use of molecular chlorine, improved condensate handling and liquor spill control ( 25 ) and at mills with lower BOD and gas chromatographic total ion profiles ( 28 , 87 ). A study of female white sucker in the Androscoggin River, Maine, USA found that the pattern of reproductive impacts observed near 3 pulp mills disappeared after a switch to ECF bleaching, including reductions in gonad size and plasma E2 and increase in plasma T in fish exposed to effluent ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…The environmental effects of emissions from the cellulose industry have, since the 1960s, been an area for environmental research forming the basis for successive mitigation actions to protect aquatic life (Norrström and Karlsson 2015 ; Ussery et al 2021 ). Numerous field studies targeting effects on fish have been conducted in Scandinavia (Sandström et al 1988 ; Landner et al 1994 ; Förlin et al 1995 ; Karels and Oikari 2000 ), North- and South America (Adams et al 1992 ; Munkittrick et al 1994 ; McMaster et al 2006 ; Chiang et al 2010 ; Mower et al 2011 ; Barra et al 2021 ) and Oceania (Harris et al 1992 ; van den Heuvel et al 2010 ). For natural reasons, most studies have focused on the effects of present emissions, whereas relatively few studies, with some exceptions (Meriläinen et al 2001 ; Hynynen et al 2004 ; Arciszewski et al 2021 ), have investigated the status of ecological indicators after mill closure.…”
mentioning
confidence: 99%